Automated mesh production for limiter Wendelstein-7X configuration - Pełka, G.; Stępniewski, W.; Zagórski, R. (Вопросы атомной науки и техники, 2017)
A tool for automated mesh production for 3D multifluid plasma transport code Findif is presented. Mesh points for the code lie on magnetic field lines, which, in general, form a complicated tangle. Open field lines that end on solid parts of the machine are the source of difficulties. These lines are usually short and thousands of them are needed. A tool that helps to pick lines for the mesh that is described in this paper is based on calculation the distances of lines already admitted to the mesh and candidate ones. The results of the code run for the limiter configuration (OP-1.1 experimental phase) of the Wendelstein-7X device are shown here. Reasonably even coverage of space by points is achieved. Представлен трёхмерный код Findif для переноса многожидкостной модели плазмы как инструмент автоматизированного производства сетки. Сетка точек для кода лежит на магнитных силовых линиях, которые, вообще говоря, образуют сложную конфигурацию. Открытые силовые линии, которые ограничены твёрдыми частями механизма, являются источником сложностей. Эти линии, как правило, короткие, и нужны тысячи из них. Инструмент, который помогает подобрать линии для сетки, описан в этой статье и основан на вычислении расстояния линий уже допущенных к сетке и кандидатов из них. Представлены результаты прогона кода для конфигурации лимитера (OP-1.1 экспериментальная фаза) стелларатора Wendelstein-7X. Представлено тривимірний код Findif для перенесення багаторідинної моделі плазми як інструмент автоматизованого виробництва сітки. Сітка точок для коду лежить на магнітних силових лініях, які, взагалі кажучи, утворюють складну конфігурацію. Відкриті силові лінії, що обмежені твердими частинами механізма, є джерелом труднощів. Ці лінії, як правило, короткі, і потрібні тисячі з них. Інструмент, який допомагає підібрати лінії для сітки, описаний в цій статті і заснований на обчисленні відстані ліній вже допущених до сітки і кандидатів з них. Представлено результати прогону коду для конфігурації лимитера (OP-1.1 експериментальна фаза) стеларатора Wendelstein-7X.